Analyzing Immune Cell Infiltration and Copper Metabolism in Diabetic Foot Ulcers - Yi WJ; Yuan Y; Bao Q; Zhao Z; Ding HS; Song J (Dove Medical Press, 2024)
Wen-Juan Yi,1,* Yifan Yuan,2,* Qionglin Bao,3 Zhuowei Zhao,4 Hua-Sheng Ding,5 Jiquan Song1 1Department of Dermatology, Zhongnan hospital of Wuhan University, Wuhan, People's Republic of China; 2Center of Gerontology and Geriatrics, West China Hospital, Sichuan University, Chengdu, People's Republic of China; 3Wound Repair Center, Chronic Wound and Diabetic Foot Clinical Medical Research Center, Liyuan Hospital Affiliated to Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China; 4Hubei Key Laboratory of Cell Homeostasis, College of Life Sciences, TaiKang Center for Life and Medical Sciences, Wuhan University, Wuhan, People's Republic of China; 5Department of Emergency, Shenzhen Hospital, Southern Medical University, Shenzhen, People's Republic of China*These authors contributed equally to this workCorrespondence: Hua-Sheng Ding; Jiquan Song, Email hsding2019@126.com; songjiq@126.comBackground: Diabetes impairs wound healing, notably in diabetic foot ulcers (DFU). Stress, marked by the accumulation of lipoylated mitochondrial enzymes and the depletion of Fe-S cluster proteins, triggers cuproptosis-a distinct form of cell death. The involvement of copper in the pathophysiology of DFU has been recognized, and currently, a copper-based therapeutic strategy is emerging as a viable option for enhancing ulcer healing. This study investigates genes linked to copper metabolism in DFU, aiming to uncover potential targets for therapeutic intervention.Methods: Two diabetic wound Gene Expression Omnibus (GEO) datasets were analyzed to study immune cell dysregulation in diabetic wounds. Differentially expressed genes related to copper metabolism were identified and analyzed using machine learning methods. Gene ontology, pathway enrichment, and immune infiltration analyses were performed using DFU samples. The expression of identified genes was validated using qRT-PCR and single-cell RNA sequencing.Results: Ten genes associated with copper metabolism were identified. Among these, SLC31A1 and ADNP were found to be significantly differentially expressed in DFU. Notably, SLC31A1 exhibited higher expression in macrophages, whereas ADNP was found to be highly expressed in fibroblasts and chondrocytes.Conclusion: The study indicates a close link between copper metabolism, the infiltration of immune cells, and DFU. It proposes that copper metabolism could influence the progression of DFU through the activation of immune responses. These observations offer fresh perspectives on the underlying mechanisms of DFU and identify potential targets for therapeutic intervention.Keywords: diabetic foot ulcers, copper metabolism, immune infiltration, single-cell RNA analysis, differentially expressed genes